Low power upconversion mixer for medical remote sensing - Lioe, De Xing; Shafie, Suhaidi; Ramiah, Harikrishnan; Tan, Gim Heng (Hindawi Publishing Corporation, 2014)
This work presents the design of a low power upconversion mixer adapted in medical remote sensing such as wireless endoscopy application. The proposed upconversion mixer operates in ISM band of 433 MHz. With the carrier power of −5 dBm, the proposed mixer has an output inferred 1 dB compression point of −0.5 dBm with a corresponding output third-order intercept point (OIP3) of 7.1 dBm. The design of the upconversion mixer is realized on CMOS 0.13 μm platform, with a current consumption of 594 μA at supply voltage headroom of 1.2 V.